1980
DOI: 10.3758/bf03213415
|View full text |Cite
|
Sign up to set email alerts
|

Lexical decision in a phonologically shallow orthography

Abstract: The Serbo-Croatian language is written in two alphabets, Roman and Cyrillic. Both orthographies transcribe the sounds of the language in a regular and straightforward fashion and may, therefore, be referred to as phonologically shallow in contrast to English orthography, which is phonologically deep. Most of the alphabet characters are unique to one alphabet or the other. There are, however, a number of shared characters, some of which receive the same reading and some of which receive a different reading, in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0

Year Published

1982
1982
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(45 citation statements)
references
References 9 publications
2
43
0
Order By: Relevance
“…Because our participants were native speakers of Hebrew, it should be clear that the Stroop effect for English-written and cross-script homophones should have been relatively small (see Magiste, 1984;Tzelgov, Henik, & Leiser, 1990). Lukatela, Popadic, Ognenovic, and Turvey (1981) distinguished between alphabets having deep or shallow orthographies. In the latter, the relation between graphemes and phonemes is simple and straightforward; thus, words are spelled the way they sound.…”
Section: Methodsmentioning
confidence: 99%
“…Because our participants were native speakers of Hebrew, it should be clear that the Stroop effect for English-written and cross-script homophones should have been relatively small (see Magiste, 1984;Tzelgov, Henik, & Leiser, 1990). Lukatela, Popadic, Ognenovic, and Turvey (1981) distinguished between alphabets having deep or shallow orthographies. In the latter, the relation between graphemes and phonemes is simple and straightforward; thus, words are spelled the way they sound.…”
Section: Methodsmentioning
confidence: 99%
“…The choice of route may, in turn, be influenced by the relative grapheme-to-phoneme transparency (or shallowness) of a writing system, as proposed in the Orthographic Depth Hypothesis or ODH (Frost, Katz, & Bentin 1987). Lukatela, Popadić, Ognjenović, and Turvey (1980) showed that readers of SerboCroatian (written in Roman and Cyrillic, with both orthographies being highly transparent) were slower at making lexical decisions to words comprised of phonologically ambiguous letters. These words have one rendition if construed as being written in Roman script and another when taken for Cyrillic; for example, POTOP in Roman means deluge, whereas in Cyrillic, it is pronounced /rotor/, meaning rotor.…”
Section: Introductionmentioning
confidence: 99%
“…Kanji and English differ in terms of their "orthographic depth", which is roughly the degree to which the pronunciation of a word can be derived from the pronunciation of its parts. Thus, Serbo-Croatian and Italian are shallow, whereas English, which is more irregular, is deeper (Frost, Katz, & Bentin, 1987;Lukatela, Popadic, Ognjenovic, & Turvey, 1980). Zorzi et al (1998b) predicted that readers differentially weight assembled phonology (i.e., the pronunciation derived from a direct spelling-sound mapping) and retrieved phonology (i.e., the pronunciation derived from lexical access) in a way that reflects the relative transparency of the mapping between spelling and sound in a specific language.…”
mentioning
confidence: 99%